2013
DOI: 10.1037/a0029258
|View full text |Cite
|
Sign up to set email alerts
|

Retraining the addicted brain: A review of hypothesized neurobiological mechanisms of mindfulness-based relapse prevention.

Abstract: Addiction has generally been characterized as a chronic relapsing condition. Several laboratory, preclinical, and clinical studies have provided evidence that craving and negative affect are strong predictors of the relapse process. These states, as well as the desire to avoid them, have been described as primary motives for substance use. A recently developed behavioral treatment, Mindfulness-Based Relapse Prevention (MBRP), was designed to target experiences of craving and negative affect and their roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 135 publications
(250 reference statements)
2
107
0
2
Order By: Relevance
“…Results indicated that both days of formal practice per week and minutes of formal practice per week reduced the strength of the relationship between craving and use. Although many investigators have hypothesized that mindfulness practice may decouple craving and subsequent use (Grow et al, 2015;Brewer et al, 2014;Garland et al, 2014;Witkiewitz, Bowen, et al, 2013;Ostafin et al, 2012), only one locatable study to date has examined mindfulness practice as a moderator of the relationship between craving and use (Elwafi et al, 2013). In a sample of tobacco smokers, results indicated days of informal practice was the only dimension of mindfulness practice that moderated the craving-use relationship (Elwafi et al, 2013).…”
Section: Summary Of Current Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results indicated that both days of formal practice per week and minutes of formal practice per week reduced the strength of the relationship between craving and use. Although many investigators have hypothesized that mindfulness practice may decouple craving and subsequent use (Grow et al, 2015;Brewer et al, 2014;Garland et al, 2014;Witkiewitz, Bowen, et al, 2013;Ostafin et al, 2012), only one locatable study to date has examined mindfulness practice as a moderator of the relationship between craving and use (Elwafi et al, 2013). In a sample of tobacco smokers, results indicated days of informal practice was the only dimension of mindfulness practice that moderated the craving-use relationship (Elwafi et al, 2013).…”
Section: Summary Of Current Findingsmentioning
confidence: 99%
“…Mindfulness Based Relapse Prevention (MBRP) is a treatment based on RP, and includes mindfulness practices focused on developing more skillful responses to craving (Bowen, Chawla, & Marlatt, 2011;Witkiewitz, Bowen, et al, 2013;Witkiewitz, Marlatt, & Walker, 2005). Mindfulness practices may increase the ability of individuals with substance use disorders to accept the unpleasant physical, affective and cognitive experiences of craving, and resist engaging in substance-seeking behavior to alleviate the discomfort (Witkiewitz et al, 2005).…”
Section: Mindfulness-based Treatment For Substance Use Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus mindfulness may be able to both sensitize to automatic processes and desensitize to negative emotions and thoughts. At a neurobiological level, mindfulness may help prevent relapse into addiction through top-down and bottom-up processes [47]. Top-down processes include increasing executive functioning, and improving attention, cognitive and emotion regulation.…”
Section: Mode Of Action Of Mindfulnessmentioning
confidence: 99%